Synthesis and properties of CO2-based plastics: Environmentally-friendly, energy-saving and biomedical polymeric materials. (May 2018) - Xu, Yonghang; Lin, Limiao; Xiao, Min; Wang, Shuanjin; Smith, Andrew T.; Sun, Luyi; Meng, Yuezhong
Abstract: Production of biodegradable plastics from carbon dioxide, particularly as a means of recycling industrial waste gas, is a promising advancement in environmental and energy conservation. Recent research and development on CO2 -based copolymers has demonstrated new approaches to achieve improvements of thermal and mechanical properties, and extension of functionalization, and practical applications. CO2 -based plastics may soon become commercially accessible as a new class of environmentally-friendly, energy-saving and biomedical polymeric materials.